THE INFLUENCE OF COFFEE PLANTATIONS' AREA, COFFEE PRODUCTION, AND RUPIAH EXCHANGE RATE TOWARDS THE GROWTH OF INDONESIA COFFEE EXPORT TO THE UNITED STATES 2000-2021 - ladi wajuba perdini fisabilillah; dinda retno kinasih (Journal of Agri Socio Economics and Business, 2023)
This study aims to determine the effect of the variable area of coffee plantations, coffee production and the rupiah exchange rate on the growth of Indonesian coffee export to the United States from 2000-2021. This research uses a quantitative approach. By using purposive sampling technique. The analysis method used is multiple linear regression. The results of this study indicate that three of independent variables have a simultaneous effect with dependent variables. The significant negative partial effect of the land area (LA), non significant negative partial effect of the exchange rate (ER) and partial positive significant of the coffee production (CP). Coffee production is dominant variable that affects the depdendent variable